Interferon β treatment for multiple sclerosis has a graduated effect on MRI enhancing lesions according to their size and pathology. Issue 3 (1st September 1999) - Filippi, M; Rovaris, M; Capra, R; Gasperini, C; Prandini, F; Martinelli, V; Horsfield, M A; Bastianello, S; Sormani, M P; Pozzilli, C; Comi, G
Abstract : OBJECTIVE: The ability of recombinant human interferon β-1a (rh-IFN β-1a) to suppress multiple sclerosis activity, evaluated from MRI, was assessed across a range of lesions enhancing at different gadolinium-DTPA (Gd) doses and with different sizes. METHODS: Every 4 weeks, standard dose (Sd; 0.1 mmol/kg Gd) and triple dose (Td; 0.3 mmol/kgGd) MRI were obtained from 18 patients with relapsing-remitting multiple sclerosis for 3 months before and 4 months after starting treatment with 44 μg rh-IFN β-1a subcutaneously, once a week. RESULTS: The total numbers of enhancing lesions were 145 and 126 on Sd scans and 278 and 192 on the Td scans obtained before and after treatment. The introduction of treatment decreased, on average, the rate of appearance of new enhancing lesions seen on Sd and Td scans by 37% (p<0.001). Treatment effects on new enhancing lesions seen on Td scans was, on average, 28% higher than on those seen on Sd scans. The distribution of lesion sizes on Td scans changed significantly during the treatment period (p=0.05), due to a marked decrease in the number of small lesions. CONCLUSIONS: The effect of 44 μg rh-IFN β-1a in reducing multiple sclerosis disease activity, as monitored by Gd enhanced MRI, is not homogeneous, but graduated according to the pathological characteristics and size of the lesions.